Construção e validação de cartilha educativa para planejamento reprodutivo de pessoas vivendo no contexto do HIV - Costa, Ana Karoline Bastos (2022)
The desire to become pregnant or to choose the best period for pregnancy in the presence of HIV is a health care need, whose reproductive counseling developed by a health professional will discuss with the woman, man or couple different situations such as clinical condition, current treatment, risks involved, reinfection, psychological aspects to identify the ideal period for the realization or not of the pregnancy. In view of this, a methodological study was carried out with the objective of building and validating a booklet aimed at the reproductive planning of people living in the context of HIV. The educational technology is entitled: “Resolving doubts about reproductive planning in the face of HIV”. The study followed the following phases: elaboration of the booklet; validation with content judges, adequacy according to the judges' suggestions and validation with the target audience. The elaboration was based on manuals from the Ministry of Health and Orem's Self-Care Deficit Theory. The population consisted of 27 content judges and 22 people living with HIV. The Flesch readability test was applied to the textual script, obtaining an index of 16.5, classifying the material as “very difficult” to read. Pages of the booklet that reached Content Validity Index (CVI) > 0.80 were considered validated. In the validation with the expert judges, the booklet showed an excellent global CVI (0.96), thus making the content validated with at least 90% agreement between the evaluators. Regarding the evaluation of the booklet through the Suitability Assessment of Materials (SAM) instrument, 91% of the material was classified by the judges as a material with a “higher” degree of recommendation to be used with the target audience, only two items were considered. assessed as adequate. Regarding the validation of appearance with the target audience, the health literacy scale was applied, it was observed that 90.9% of the participants (n=20) have high literacy. When the essay questionnaire was applied to evaluate the booklet, 100% agreement was observed in most items. All participants reported that the figures presented help a better understanding of the subject. When evaluating the clarity of the topics covered in the booklet, all pages of the booklet were more than 95% clear. When evaluating the relevance of the subjects covered in the booklet, all pages of the booklet had more than 100% agreement. The final version of the booklet consists of 42 pages. It can be concluded that the technology developed is valid, with a high degree of recommendation by expert judges to be used with people living with HIV.